Hydrogen Saturation of Aluminum Alloys during Atmospheric Corrosion - Laptev Anatoly; Abramova Maria; Lonskaya Nataly; Davydov Dmitry; Averina Alena (Innovations in Science and Technology Vol. 3, 2022)
The results of a study of hydrogen saturation during corrosion of aluminum alloys of eight alloying systems are presented. The tests were carried out for four years with additional irrigation with chloride solutions in a moderately warm climate. It is shown that during corrosion, intense saturation of alloys with hydrogen occurs. The type of corrosion - with intercrystalline corrosion, determines the amount of hydrogen in the alloy hydrogen penetration occurs more intensively than with pitting and delaminating corrosion. The mechanism of hydrogen saturation of alloys is proposed. The change in the energy of an aluminum crystal during the blockage of atomic hydrogen and the formation of a hydrogen molecule are determined by quantum chemical calculations. The relationship between the plasticity of the tested aluminum alloy alloys and the intensity of hydrogen saturation is shown.